A spraying method of a strong interface bonding biomimetic layer-pillar composite structure coating
Patent Information
- Application Number
- CN202611050110.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-06-02
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-27
AI Technical Summary
[0017]本发明的创新点在于:在大气等离子喷涂过程中,通过变位机带动试样平面旋转,制备得到螺旋位错层状结构环境障涂层,通过激光重熔技术同步在每层陶瓷层表面制备微米级仿生小柱结构。平面旋转喷涂形成的螺旋交错层状结构可有效分散热循环应力、提升致密度与界面结合,而微米级仿生小柱单元体内的柱状晶与微型垂直裂纹赋予涂层优异的应变容限,二者协同释放热应力,显著提高涂层抗热震性能。
Smart Images

Figure CN122977871A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental barrier coatings and their surface modification, and specifically relates to a method for spraying a biomimetic layer-columnar composite structure coating with strong interfacial bonding. Background Technology
[0002] With the development of the aerospace industry, traditional nickel-based superalloys can no longer meet the high-temperature service requirements of hot-end components in aero-engines. In the temperature range of 1300~1500℃, ceramic matrix composites have emerged as a promising candidate material due to their advantages of low density, high strength, and high temperature resistance, becoming important candidates for next-generation advanced military aero-engine hot-end components. To address their poor chemical stability in high-temperature water and oxygen environments, environmental barrier coatings (EBCs) have been developed. Rare earth silicates (Yb₂SiO₃) 7、 Yb2Si2O7 has good phase stability, excellent resistance to water and oxygen corrosion and a low coefficient of thermal expansion, making it one of the key components of environmental barrier coatings.
[0003] Currently, widely used environmental barrier coatings consist of a ceramic matrix composite matrix, an adhesive layer, and a surface ceramic coating. The adhesive layer, located between the ceramic layer and the ceramic matrix composite matrix, primarily enhances the adhesion between the ceramic layer and the matrix, and protects the matrix from oxidation and corrosion. Si and silicon-based alloys are commonly used adhesive layer materials in environmental barrier coating systems. Elemental Si is widely used as the adhesive layer in environmental barrier coatings due to its good thermal expansion matching with the SiC matrix and its excellent high-temperature oxidation resistance. The ceramic layer is the outermost layer of the EBC, directly in contact with high-temperature gases, and its main function is to provide environmental insulation. Rare earth silicates (Yb₂SiO₃) are also used. 7、 Yb2Si2O7 is a ceramic surface material with great application potential in environmental barrier coatings due to its excellent resistance to water and oxygen corrosion and good high-temperature phase stability.
[0004] With the advancement of aero-engine technology, the operating environment of hot-end components such as turbine blades and exhaust nozzles under high-temperature conditions is becoming increasingly harsh. Environmental barrier coatings face various problems and challenges, such as thermal expansion coefficient mismatch, high-temperature oxidation, and corrosion. Traditional environmental barrier coatings have a dense or disordered porous ceramic layer with a mismatch in thermal expansion coefficients with the bonding layer. This leads to interfacial stress concentration during thermal cycling, and cracks tend to propagate rapidly along continuous paths. The thermal fatigue failure process of environmental barrier coatings is actually a process of interfacial thermal stress accumulation, crack initiation and propagation, and ultimately, coating peeling.
[0005] Given the existing problems with environmental barrier coatings, the use of laser technology combined with atmospheric plasma spraying to improve their thermal shock resistance has attracted attention from experts and scholars both domestically and internationally. Two main research methods exist: one is laser remelting, a technique that uses a high-energy laser beam to rapidly heat and cool the material surface, altering its surface structure, composition, and properties; the other is laser alloying, which uses the high energy density of a laser beam to rapidly melt the substrate surface and mix it with alloying elements to form a new alloy layer, thereby improving the substrate's surface properties. However, these methods result in high residual stress within the coating and severe cracking, failing to effectively improve the performance of environmental barrier coatings. Therefore, further research is urgently needed to explore ways to improve the thermal shock resistance of environmental barrier coatings. Summary of the Invention
[0006] To address the aforementioned problems, this invention proposes a method for spraying a biomimetic layer-column composite structure coating with strong interfacial bonding. The concept involves using biomimetic principles and combining laser technology with atmospheric plasma spraying technology to prepare a composite environmental barrier coating that has both a micron-level biomimetic columnar structure and a spiral interlaced layered structure.
[0007] S1. The SiC ceramic matrix composite material matrix is cleaned and sandblasted; S2. The substrate is preheated, and then an adhesive layer is prepared on the Si or MoSi2 substrate by atmospheric plasma spraying. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, spraying distance 100~110mm, and the adhesive layer thickness is 80~120μm. Next, a ceramic layer of medium-heavy rare earth silicates is sprayed onto the adhesive layer. The spraying parameters are: current 500-700A, argon flow rate 40-50L / min, hydrogen flow rate 1-5L / min, spraying speed 90-110mm / s, powder feed rate 10-20g / min, and spraying distance 100-110mm. The thickness of the ceramic layer is 200-300μm. The obtained sample is transferred to a laser remelting stage. S3. A micron-sized column array is sequentially processed on the surface of the ceramic layer using a pulsed laser. The laser power of the pulsed laser is 200-500W, the spot diameter is 150-200μm, the scanning speed is 200-800mm / s, and the overlap rate is 40%-70%. The sample plane is rotated 30-60 degrees relative to the previous spraying direction. S4. Repeat S3 four to six times to complete the spraying.
[0008] More specifically, step S3 includes: S3.1 Using the pulsed laser of the pulsed laser remelting stage, a 5×5 array of micron-sized pillars was formed on the surface of the ceramic layer. The pulsed laser was set with the following parameters: processing time 2ms, frequency 20kHz, and pulse width 20μs. The sample was then clamped and reset. S3.2 Rotate the sample plane 30-60 degrees relative to the previous layer spraying direction using a positioner.
[0009] More specifically, the cleaning described in S1 is performed using ultrasonic cleaning with an ultrasonic power of 240W in anhydrous ethanol with a purity of 95%.
[0010] More specifically, the material of the SiC ceramic matrix composite matrix described in S1 is silicon carbide fiber reinforced silicon carbide ceramic matrix composite (SiC). f One of the following: (C / SiC) or carbon fiber reinforced silicon carbide composite (C / SiC).
[0011] More specifically, the SiC ceramic matrix composite material matrix described in S1 is sandblasted to a surface roughness of Ra 8~10 μm.
[0012] More specifically, the preheating treatment described in S2 is spraying under a plasma arc with a current of 300A, an argon flow rate of 45L / min, and a hydrogen flow rate of 1L / min. After preheating, the surface temperature of the substrate is between 200 and 300 degrees Celsius.
[0013] More specifically, the medium-heavy rare earth silicate mentioned in S2 is Yb2SiO5 or Yb2Si2O7.
[0014] More specifically, the overlap ratio of the pulsed laser described in S3 is 40%.
[0015] More specifically, the diameter of the micron-sized column described in S3.1 is 200~600μm, the height is 30~90μm, and the distance between the centers of adjacent micron-sized columns is 3~5 mm.
[0016] More specifically, the steps of the strong interface bonding biomimetic layer-columnar composite structure coating spraying method include: S1. Silicon carbide fiber-reinforced silicon carbide ceramic matrix composite (SiC) f The C / SiC matrix or carbon fiber reinforced silicon carbide composite (C / SiC) matrix was placed in 95% pure anhydrous ethanol and ultrasonically cleaned for 15 minutes using 240W to remove impurities from the matrix surface. Then, it was dried in an environment of 60~70°C until the anhydrous ethanol was completely evaporated. Then, the surface was sandblasted until the surface roughness was measured to be Ra 8~10μm by three-dimensional confocal microscopy. S2. The substrate is preheated, and then an adhesive layer is prepared on the substrate by atmospheric plasma spraying with Si or MoSi2 material. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, spraying distance 100~110mm, and the adhesive layer thickness is 80~120μm. A medium-heavy rare earth silicate ceramic layer is sprayed onto the surface of the adhesive layer. The medium-heavy rare earth silicate is Yb2SiO5 or Yb2Si2O7. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, and spraying distance 100~110mm. The thickness of the ceramic layer is 200-300μm. The obtained sample was transferred to a laser remelting stage; S3. Using a pulsed laser, a micron-scale array of small pillars is sequentially fabricated on the surface of the ceramic layer: S3.1 Using the pulsed laser of the laser remelting stage, a 5×5 array of micron-sized pillars is formed on the surface of the ceramic layer. The diameter of the micron-sized pillars is 200~600μm, the height is 30~90μm, and the distance between the centers of adjacent micron-sized pillars is 3~5mm; then the sample is clamped and reset. The laser parameters of the pulsed laser are: Laser power of 200~500W, spot diameter of 150~200μm, scanning speed of 200~800mm / s, and overlap rate of 40%~70%; The pulsed laser was set with the following parameters: processing time 2ms, frequency 20kHz, and pulse width 20μs. S3.2 Rotate the sample plane 30-60 degrees relative to the previous layer spraying direction using a positioner; S4. Repeat S3 four to six times to complete the spraying and obtain the finished product.
[0017] The innovation of this invention lies in the following: During atmospheric plasma spraying, a positioner drives the sample plane to rotate, thus preparing a spiral dislocation layered environmental barrier coating. Simultaneously, micron-scale biomimetic columnar structures are fabricated on the surface of each ceramic layer using laser remelting technology. The spiral interlaced layered structure formed by planar rotational spraying effectively disperses thermal cycling stress, improves density and interfacial bonding, while the columnar crystals and micro-vertical cracks within the micron-scale biomimetic columnar units endow the coating with excellent strain tolerance. These two elements synergistically release thermal stress, significantly improving the coating's thermal shock resistance.
[0018] The beneficial effects of this invention include: the preparation of micron-scale columnar biomimetic unit cells on each ceramic layer using laser remelting technology; the spiral interlaced layered structure can disperse thermal cycling stress and optimize coating density; laser remelting eliminates coating defects and forms dense columnar crystals, obtaining high-hardness biomimetic unit cells, increasing crack propagation resistance; at the same time, the biomimetic columnar unit cells and the spiral interlaced layered structure synergistically improve the coating strain tolerance, delay crack propagation, cut off crack propagation paths, and extend the service life of the coating. Attached Figure Description
[0019] Figure 1 This is a laser remelting process diagram of the strong interface bonding biomimetic layer-column composite structure coating spraying method of the present invention.
[0020] Figure 2 This is a structural diagram of a micrometer-scale columnar array according to an embodiment of the present invention.
[0021] Figure 3 This is a cross-sectional structural diagram of the sprayed environmental barrier coating of the present invention.
[0022] Figure 4 This is a cross-sectional structural diagram of the biomimetic layer-column composite environmental barrier coating of Embodiment 1 of the present invention.
[0023] Figure 5 This is a cross-sectional structural diagram of the biomimetic layer-column composite environmental barrier coating of Embodiment 2 of the present invention.
[0024] Figure 6 This is a cross-sectional structural diagram of the biomimetic layer-column composite environmental barrier coating of Embodiment 3 of the present invention. Detailed Implementation
[0025] Example 1
[0026] S1. Silicon carbide fiber-reinforced silicon carbide ceramic matrix composite (SiC) f The SiC substrate was placed in 95% anhydrous ethanol and ultrasonically cleaned for 15 minutes using 240W to remove impurities from the coating surface. It was then dried at 60-70°C until the anhydrous ethanol completely evaporated. The surface was then sandblasted until the surface roughness, as measured by a three-dimensional confocal microscope, was Ra 8-10 μm.
[0027] S2. The prepared substrate is fixed in a fixture and placed on a workbench. Preheating treatment is performed by plasma arc spraying with a current of 300A, an argon flow rate of 45L / min, and a hydrogen flow rate of 1L / min. A Si bonding layer is prepared on the substrate surface by atmospheric plasma spraying. The bonding layer spraying parameters are: current intensity of 550A, spraying distance of 110mm, spraying speed of 100mm / s, and powder feeding rate of 15g / min. A Yb2Si2O7 ceramic layer was sprayed onto the surface of the adhesive layer. The process parameters for atmospheric plasma spraying were: current intensity 650A, spraying distance 100mm, spraying speed 100mm / s, and powder feeding rate 15g / min. S3. Transfer the sample to the pulsed laser remelting stage; set the laser parameters as follows: processing time 2ms, frequency 20kHz, pulse width 20μs. The laser parameters for laser remelting are: laser power 200W, laser scanning speed 300mm / s, laser spot diameter 175μm, and spot overlap rate 40%. A 5×5 array of micron-sized pillars is fabricated on the surface of a ceramic layer using a pulsed laser on a pulsed laser remelting stage; the structure of the micron-sized pillar array is as follows: Figure 2 As shown, the diameter of the micron-sized column is 300 μm, and the center-to-center distance between adjacent micron-sized columns is 3 mm.
[0028] The sample is then clamped and reset, and the sample is rotated 30 degrees by a positioner before the next ceramic layer is sprayed. S4. For example Figure 1 As shown, repeat S3 four times to obtain the finished product.
[0029] In this embodiment, the adhesive layer of the environmental barrier coating has a thickness of 100 μm, the ceramic layer has a thickness of 220 μm, and the height of the laser-remelted micron-sized pillars is 30 μm. For example... Figure 3 As shown, the plasma-sprayed ceramic layer exhibits obvious defects such as pores, voids, and microcracks. After laser remelting modification of the ceramic layer, the coating structure becomes dense and uniform, but columnar crystal structures and vertical cracks are produced, such as... Figure 4 As shown, the gaps between columnar and bulk crystals can improve the strain tolerance of the coating at high temperatures. This structure allows thermal stress to be released, thereby improving the thermal shock resistance of the coating. Through analysis and calculation, compared with the pure spray coating, the biomimetic layer-column composite structure environmental barrier coating improves the thermal shock resistance of the coating, increases the microhardness by 10%, and increases the number of thermal cycles by 16%.
[0030] Example 2
[0031] S1. Silicon carbide fiber-reinforced silicon carbide ceramic matrix composite (SiC) f The SiC substrate was placed in 95% anhydrous ethanol and ultrasonically cleaned for 15 minutes using 240W to remove impurities from the coating surface. It was then dried at 60-70°C until the anhydrous ethanol completely evaporated. The surface was then sandblasted until the surface roughness, as measured by a three-dimensional confocal microscope, was Ra 8-10 μm. S2. The prepared substrate is fixed in a fixture and placed on a workbench. Preheating treatment is performed by plasma arc spraying with a current of 300A, an argon flow rate of 45L / min, and a hydrogen flow rate of 1L / min. A Si bonding layer is prepared on the substrate surface by atmospheric plasma spraying. The bonding layer spraying parameters are: current intensity of 550A, spraying distance of 110mm, spraying speed of 100mm / s, and powder feeding rate of 15g / min. A Yb2Si2O7 ceramic layer was sprayed onto the surface of the adhesive layer. The process parameters for atmospheric plasma spraying were: current intensity 650A, spraying distance 100mm, spraying speed 100mm / s, and powder feeding rate 15g / min. S3. Transfer the sample to the pulsed laser remelting stage; set the laser parameters as follows: processing time 2ms, frequency 20kHz, pulse width 20μs. The laser parameters for laser remelting are: laser power 300W, laser scanning speed 400mm / s, laser spot diameter 175μm, and spot overlap rate 40%. A 5×5 array of micron-sized pillars was fabricated on the surface of a ceramic layer using a pulsed laser on a pulsed laser remelting stage. The diameter of the micron-sized pillars in the array was 400 μm, and the center-to-center distance between adjacent micron-sized pillars was 4 mm.
[0032] The sample is then clamped and reset, and the sample is rotated 45 degrees by a positioner before the next ceramic layer is sprayed. S4. Repeat S3 four times to obtain the finished product.
[0033] In this embodiment, the adhesive layer of the environmental barrier coating has a thickness of 100 μm, the ceramic layer has a thickness of 220 μm, and the height of the laser-remelted biomimetic columnar unit is 60 μm. For example... Figure 3 As shown, the plasma-sprayed ceramic layer exhibits obvious defects such as pores, voids, and microcracks. After laser remelting modification of the ceramic layer, the coating structure becomes dense and uniform, but columnar crystal structures and vertical cracks are generated, such as... Figure 5 As shown, the gaps between columnar and bulk crystals can improve the strain tolerance of the coating at high temperatures. This structure allows thermal stress to be released, thereby improving the thermal shock resistance of the coating. Through analysis and calculation, compared with the pure spray coating, the biomimetic layer-columnar composite structure environmental barrier coating improves the thermal shock resistance of the coating, increases the microhardness by 19%, and increases the number of thermal cycles by 25%.
[0034] Example 3
[0035] S1. Silicon carbide fiber-reinforced silicon carbide ceramic matrix composite (SiC) fThe SiC substrate was placed in 95% anhydrous ethanol and ultrasonically cleaned for 15 minutes using 240W to remove impurities from the coating surface. It was then dried at 60-70°C until the anhydrous ethanol completely evaporated. The surface was then sandblasted until the surface roughness, as measured by a three-dimensional confocal microscope, was Ra 8-10 μm. S2. Place the treated substrate in a fixture and fix it. Place it on the workbench and preheat it by plasma arc spraying with a current of 300A, an argon flow rate of 45L / min, and a hydrogen flow rate of 1L / min. After preheating, the surface temperature of the substrate is 200~300 degrees. A Si bonding layer was prepared on the substrate surface by atmospheric plasma spraying. The spraying parameters for the bonding layer were: current intensity 550A, spraying distance 110mm, spraying speed 100mm / s, and powder feeding rate 15g / min. A Yb2Si2O7 ceramic layer was sprayed onto the surface of the adhesive layer. The process parameters for atmospheric plasma spraying were: current intensity 650A, spraying distance 100mm, spraying speed 100mm / s, and powder feeding rate 15g / min. S3. (1) After completing the deposition of a single ceramic layer by atmospheric plasma spraying, the sample is transferred to a pulsed laser remelting stage; (2) Using the pulsed laser of the pulsed laser remelting stage, the laser is set with the following parameters: processing time 2ms, frequency 20KHz, pulse width 20μs. A 5×5 array of micron-sized pillars is formed on the surface of the ceramic layer. The diameter of the micron-sized pillars is 500μm and the center distance between adjacent micron-sized pillars is 5mm. The sample is then clamped and reset; (3) The sample plane is rotated 60 degrees relative to the previous layer spraying direction by a positioner before the next layer of ceramic layer is sprayed. The laser parameters used for laser remelting are: laser power 400W, laser scanning speed 500mm / s, laser spot diameter 175μm, and spot overlap rate 40%; S4. Repeat S3 four times to obtain the finished product.
[0036] In this embodiment, the adhesive layer of the environmental barrier coating has a thickness of 100 μm, the ceramic layer has a thickness of 220 μm, and the height of the laser-remelted biomimetic columnar unit is 90 μm. For example... Figure 3 As shown, the plasma-sprayed ceramic layer exhibits obvious defects such as pores, voids, and microcracks. After laser remelting modification of the ceramic layer, the coating structure becomes dense and uniform, but columnar crystal structures and vertical cracks are generated, such as... Figure 6As shown, the gaps between columnar and bulk crystals can improve the strain tolerance of the coating at high temperatures. This structure allows thermal stress to be released, thereby improving the thermal shock resistance of the coating. Through analysis and calculation, compared with the pure spray coating, the biomimetic layer-column composite structure environmental barrier coating improves the thermal shock resistance of the coating, increases the microhardness by 26%, and increases the number of thermal cycles by 34%.
Claims
1. A method for spraying a biomimetic layer-columnar composite structure coating with strong interfacial bonding, comprising the following steps: S1. The SiC ceramic matrix composite material matrix is cleaned and sandblasted; S2. The substrate is preheated, and then an adhesive layer is prepared on the Si or MoSi2 substrate by atmospheric plasma spraying. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, spraying distance 100~110mm, and the adhesive layer thickness is 80~120μm. Next, a ceramic layer of medium-heavy rare earth silicates is sprayed onto the adhesive layer. The spraying parameters are: current 500-700A, argon flow rate 40-50L / min, hydrogen flow rate 1-5L / min, spraying speed 90-110mm / s, powder feed rate 10-20g / min, and spraying distance 100-110mm. The thickness of the ceramic layer is 200-300μm. The obtained sample is transferred to a laser remelting stage. S3. A micron-sized column array is sequentially processed on the surface of the ceramic layer using a pulsed laser. The laser power of the pulsed laser is 200-500W, the spot diameter is 150-200μm, the scanning speed is 200-800mm / s, and the overlap rate is 40%-70%. The sample plane is rotated 30-60 degrees relative to the previous spraying direction. S4. Repeat S3 four to six times to complete the spraying.
2. The method for spraying a strong interface bonding biomimetic layer-column composite structure coating according to claim 1, characterized in that, Step S3 includes: S3.1 Using the pulsed laser of the pulsed laser remelting stage, a 5×5 array of micron-sized pillars was formed on the surface of the ceramic layer. The pulsed laser was set with the following parameters: processing time 2ms, frequency 20kHz, and pulse width 20μs. The sample was then clamped and reset. S3.2 Rotate the sample plane 30-60 degrees relative to the previous layer spraying direction using a positioner.
3. The method for spraying a strong interface bonding biomimetic layer-column composite structure coating according to claim 1, characterized in that, The cleaning described in S1 is performed using ultrasonic cleaning with an ultrasonic power of 240W in anhydrous ethanol with a purity of 95%.
4. The spraying method for a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 1, characterized in that: The material of the SiC ceramic matrix composite material matrix mentioned in S1 is silicon carbide fiber reinforced silicon carbide ceramic matrix composite material (SiC). f One of the following: (C / SiC) or carbon fiber reinforced silicon carbide composite (C / SiC).
5. The method for spraying a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 1, characterized in that: The SiC ceramic matrix composite material matrix described in S1 is sandblasted to a surface roughness of Ra 8~10 μm.
6. The method for spraying a strong interface bonding biomimetic layer-column composite structure coating according to claim 1, characterized in that, The preheating treatment described in S2 is spraying under a plasma arc with a current of 300A, an argon flow rate of 45L / min, and a hydrogen flow rate of 1L / min. After preheating, the surface temperature of the substrate is between 200 and 300 degrees Celsius.
7. The method for spraying a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 1, characterized in that: The medium-heavy rare earth silicate mentioned in S2 is Yb2SiO5 or Yb2Si2O7.
8. The method for spraying a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 1, characterized in that, The overlap ratio of the pulsed laser described in S3 is 40%.
9. The method for spraying a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 2, characterized in that: The diameter of the micron-sized column described in S3.1 is 200~600μm, the height is 30~90μm, and the distance between the centers of adjacent micron-sized columns is 3~5 mm.
10. The method for spraying a strong interface bonding biomimetic layer-columnar composite structure coating according to claim 1, comprising the following steps: S1. Silicon carbide fiber-reinforced silicon carbide ceramic matrix composite (SiC) f The C / SiC matrix or carbon fiber reinforced silicon carbide composite (C / SiC) matrix was placed in 95% pure anhydrous ethanol and ultrasonically cleaned for 15 minutes using 240W to remove impurities from the matrix surface. Then, it was dried in an environment of 60~70°C until the anhydrous ethanol was completely evaporated. Then, the surface was sandblasted until the surface roughness was measured to be Ra 8~10μm by three-dimensional confocal microscopy. S2. The substrate is preheated, and then an adhesive layer is prepared on the substrate by atmospheric plasma spraying with Si or MoSi2 material. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, spraying distance 100~110mm, and the adhesive layer thickness is 80~120μm. A medium-heavy rare earth silicate ceramic layer is sprayed onto the surface of the adhesive layer. The medium-heavy rare earth silicate is Yb2SiO5 or Yb2Si2O7. The spraying parameters are: current 500~700A, argon flow rate 40~50L / min, hydrogen flow rate 1~5L / min, spraying speed 90~110mm / s, powder feeding rate 10~20g / min, and spraying distance 100~110mm. The thickness of the ceramic layer is 200-300μm. The obtained sample was transferred to a laser remelting stage; S3. Using a pulsed laser, a micron-scale array of small pillars is sequentially fabricated on the surface of the ceramic layer: S3.1 Using the pulsed laser of the laser remelting stage, a 5×5 array of micron-sized pillars is formed on the surface of the ceramic layer. The diameter of the micron-sized pillars is 200~600μm, the height is 30~90μm, and the distance between the centers of adjacent micron-sized pillars is 3~5mm; then the sample is clamped and reset. The laser parameters of the pulsed laser are: Laser power is 200~500W, spot diameter is 150~200μm, scanning speed is 200~800mm / s, and overlap rate is 40%~70%; The pulsed laser was set with the following parameters: processing time 2ms, frequency 20kHz, and pulse width 20μs. S3.2 Rotate the sample plane 30-60 degrees relative to the previous layer spraying direction using a positioner; S4. Repeat S3 four to six times to complete the spraying and obtain the finished product.